2021
DOI: 10.3390/insects12030218
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Feeding Deterrence to 20-Hydroxyecdysone for Three Subterranean Termite Species (Blattodea: Rhinotermitidae)

Abstract: Effective active ingredients in toxicant bait formulations must be non-deterrent to insect feeding behavior at lethal concentrations. This study evaluated feeding deterrence for Coptotermes formosanus Shiraki, C. gestroi (Wasmann), and Reticulitermes flavipes (Kollar) when provided access to cellulose impregnated with various concentrations of the insect molting hormone, 20-hydroxyecdysone (20E). Termites were exposed to 20E concentrations of 200, 500, 1000 and 2000 ppm and to noviflumuron at 5000 ppm in a 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…The rate of termite consumption tends to increase with the higher concentration of basil leaf extract. In line with this result, Carnohan et al (2021) stated the concentration of extract was influence the feeding activity of termites. Some extract with higher concentration tend to increase the preference of termite to feed the bait.…”
Section: Bait Weight Losssupporting
confidence: 59%
“…The rate of termite consumption tends to increase with the higher concentration of basil leaf extract. In line with this result, Carnohan et al (2021) stated the concentration of extract was influence the feeding activity of termites. Some extract with higher concentration tend to increase the preference of termite to feed the bait.…”
Section: Bait Weight Losssupporting
confidence: 59%
“…One hundred workers and 10 soldiers were placed in each Petri dish. While previous studies provided promising results for 20E such as mortality, target concentration, and faster lethal time than CSIs, [43][44][45] the current study revealed some limitations for the potential use of 20E against subterranean termites. Based on the present study, we argue that 20E cannot be used as a sole AI to eliminate termite colonies.…”
Section: Discussionmentioning
confidence: 68%
“…8,43,44 To reduce the time taken for colony elimination, 20E, ecdysone, and halofenozide (ecdysone agonists) were tested against the economically important subterranean termites R. flavipes, C. formosanus and C. gestroi. [43][44][45] Results from previous studies suggested that 20E satisfied all requirements to be used as an AI for colony elimination: slow acting, non-repellent, and doseindependent lethal time. Thus far, at the individual level, application of 20E showed promising results, with mortality occurring after about 10 days and intoxicated termites dying from hyperecdysonism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations